Realitas Sosial dalam Novel “Ayahku Bukan Pembohong” Karya Tere Liye - Bangkit Adi Swasono (CV. Aksara Global, 2024)
This research aims to identify and analyze the social values contained in the novel Ayahku Bukan Pembohong by Tere Liye. The selection of such a novel is because it contains many elements of social value both in the context of the individual, family and society. In this study the author will discuss several formula problems with the following coverage: 1) How is the social value of the relationship of the main character with his peers in the novel Ayahku Bukan Pembohong by Tere Liye? 2) How does the social values of the relation of the main character with family in the novel Ayahku Bukan Pembohong by Tere Liye? 3) How is the sosial value of the relationship of the main character with society in the novel Ayahku Bukan Pembohong by Tere Liye? This research uses a descriptive method of culiatative. These stages of research are data collection, data reduction, data display, conclusion making or verification. From this research it can be concluded that man is one of the social beings that is inseparable from the other individuals to a purpose in life. Simple social interaction is a complex process, because it is based on several factors, both individualistic and combined. Social conflict is a social process in which individuals or groups seek to their goals by opposing opponents accompanied by threats or violence. Such circumstances can lead to conflict and even debate among human groups. But on the other hand, social conflict can also lead to positive changes in societies, trigger reform, correct injustice, and drive social change that is supposed to be necessary. Social change refers to a transformation in the structure, values, norms, cultures, and social interactions in a society that then affects a change in human attitudes. Social change affects the attitudes of human beings in society in a variety of ways, such as the adoption of a new value, changes in social norms or changes in habits and patterns of behavior.